Religious Coexistence and Legal Pluralism in Albania: Socio-Political and Legal Perspectives - Dorian Rrapi (European Scientific Journal, ESJ, 2025)
This article provides a comprehensive examination of Albania’s religious coexistence from both socio-political and legal perspectives, highlighting how historical experiences, legal frameworks, and community practices collectively shape interfaith relations. Drawing on case studies from urban centers such as Tirana and Shkodër, as well as rural communities where traditional interfaith networks have persisted, the study explores how legal pluralism, allowing religious communities to manage personal matters like marriage, inheritance, and education, interacts with grassroots social engagement to sustain harmony among Albania’s diverse religious groups.  The research also analyzes institutional policies, including the role of the State Committee on Cults, municipal interfaith programs, and the Interreligious Council of Albania (IRCA), demonstrating how coordinated initiatives between government bodies and civil society promote dialogue, joint cultural events, and collaborative social projects. By tracing the historical trajectory from the Ottoman millet system through the challenges of the communist period to contemporary reforms, the article illustrates the resilience of interfaith tolerance in Albania. This experience provides a distinctive model of religious coexistence, offering valuable lessons for other pluralistic societies in the Balkans and beyond, emphasizing the importance of combining legal recognition, social cooperation, and community-led initiatives to foster enduring interfaith harmony.